2022
DOI: 10.1007/s40120-022-00384-2
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Assessment of Quality of Life in Patients with Relapsing Remitting Multiple Sclerosis Treated with Teriflunomide for Two Years: Patient-Reported Outcomes from the AURELIO Study in Greece

Abstract: Introduction Multiple sclerosis (MS) is a highly heterogeneous inflammatory disease of the central nervous system. Patient-reported outcomes (PROs) in a real-world clinical setting can provide detailed information about MS from the patient's perspective. PROs were used here to assess quality of life (QoL), treatment satisfaction, clinical efficacy, and safety outcomes in a Greek cohort of relapsing remitting MS (RRMS) patients treated with oral teriflunomide (14 mg/day). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…clinical studies with a follow-up period of 2 years on teriflunomidetreated patients can be found so far. They all agree that after 2 years of treatment, there is an improvement compared to the baseline cognitive state in patients who are in a stable condition with therapy, which is related to the effect of treatment [30][31][32]. Our results also imply some role of therapy escalation; however, the significant impact could only be measured in case of BVMT-R scores, unlike in the teriflunomide follow-up cohorts.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…clinical studies with a follow-up period of 2 years on teriflunomidetreated patients can be found so far. They all agree that after 2 years of treatment, there is an improvement compared to the baseline cognitive state in patients who are in a stable condition with therapy, which is related to the effect of treatment [30][31][32]. Our results also imply some role of therapy escalation; however, the significant impact could only be measured in case of BVMT-R scores, unlike in the teriflunomide follow-up cohorts.…”
Section: Discussionsupporting
confidence: 69%
“…Regarding the prevalence of definitive CI, while 44.2% of the patients were cognitively impaired at baseline, the proportion was reduced to 27.9% after 5 years and 19% by the end of the study. The earlier mentioned validation cohort follow-ups and shorter duration follow-up studies with patients on teriflunomide treatment have also yielded similar results [27][28][29][30][31][32]. There are multiple possible reasons behind these aforementioned outcomes.…”
Section: Discussionmentioning
confidence: 57%
“…4−6 Accordingly, disease-modifying therapies (DMTs) approved by the U.S. Food and Drug Administration (FDA) mainly focus on inhibiting lymphocytes proliferation, including interferon beta (IFN-β), 7 glatiramer acetate (GA), 8 monoclonal antibodies (natalizumab, alemtuzumab, daclizumab and ocrelizumab), 9−11 mitoxantrone, 12 fingolimode, 13 dimethyl fumarates, 14 and teriflunomide. 15 Although these drugs reduce disease recurrence, they do not repair damaged myelin.…”
mentioning
confidence: 99%
“…MS patients or experimental models (i.e., experimental autoimmune encephalomyelitis, EAE) are characterized by T cell-mediated demyelination. , The blood–brain barrier (BBB) in MS patients is compromised, resulting in an uncontrolled influx of peripheral immune cells . Specifically, myelin-specific T cells infiltrate into the central nervous system (CNS) and attack myelin sheath to induce neuronal injury. Accordingly, disease-modifying therapies (DMTs) approved by the U.S. Food and Drug Administration (FDA) mainly focus on inhibiting lymphocytes proliferation, including interferon beta (IFN-β), glatiramer acetate (GA), monoclonal antibodies (natalizumab, alemtuzumab, daclizumab and ocrelizumab), mitoxantrone, fingolimode, dimethyl fumarates, and teriflunomide . Although these drugs reduce disease recurrence, they do not repair damaged myelin.…”
mentioning
confidence: 99%